DOES FRIENDSHIP MEDIATE THE EFFECT OF EMOTION REGULATION ON TEACHERS' SUBJECTIVE WELL BEING? SEM ANALYSIS - Nurhasanah; Hasanuddin; Nefi Darmayanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Low subjective well-being tends to underestimate their life. The purpose of this study was to determine the effect of emotional regulation on the subjective well-being of honorary RA teachers through friendship as a mediator. Quantitative research method. Sample of 288 teachers. Data collection instrument questionnaire. Data analysis using SEM PLS 4. Research results (1) Emotional regulation affects teachers' subjective well-being. (2) Friendship affects teachers' subjective well-being. (3) Friendship mediates the effect of emotional regulation on teachers' subjective well-being.